Purification and ultra-high-performance liquid chromatography tandem mass spectrometry analysis of phenolics extracted from male walnut flowers. Issue 1 (31st December 2022) - Yu, Chenchen; Li, Shengyun; Zhang, Xuemei; Ma, Aijin; Cao, Zhixiang; Qi, Guohui; Guo, Suping; tian, Yiling
ABSTRACT: In this study, phenolics extracted from male walnut flowers were purified and analyzed by ultra-high-performance liquid chromatography tandem mass spectrometry. After ultrasonic extraction of male walnut flowers with 60% ethanol, AB-8, D3520, NKA-9, D101, and NKA macroporous adsorption resins were compared for purification. The AB-8 macroporous resin gave the best adsorption and desorption performance for 0.7 mg gallic acid equivalents/mL samples (pH 3.0) loaded at a flow rate of 1 mL/min. Elution was carried out with 50% ethanol without pH adjustment. The purity of the phenolics in the eluate (72.5%) was 3.1 times that in the original extract. Analysis by ultra-high-performance liquid chromatography tandem mass spectrometry identified 16 compounds, including phenolic acids, flavonoids, and coumarins in the purified phenolics. The most abundant compounds were chlorogenic acid, kaempferol, and methoxycoumarin. Two compounds were got in male walnut flowers for the first time, and those need yet to be proved by further experiments.